Epigenetics of methylation modifications in diabetic cardiomyopathy - Hao, Jing; Liu, Yao (Frontiers in Endocrinology, 2023)
Type 2 diabetes is one of the most common metabolic diseases with complications including diabetic cardiomyopathy and atherosclerotic cardiovascular disease. Recently, a growing body of research has revealed that the complex interplay between epigenetic changes and the environmental factors may significantly contribute to the pathogenesis of cardiovascular complications secondary to diabetes. Methylation modifications, including DNA methylation and histone methylation among others, are important in developing diabetic cardiomyopathy. Here we summarized the literatures of studies focusing on the role of DNA methylation, and histone modifications in microvascular complications of diabetes and discussed the mechanism underlying these disorders, to provide the guidance for future research toward an integrated pathophysiology and novel therapeutic strategies to treat or prevent this frequent pathological condition.